Profitability Analysis of Beef Cattle Fattening Businesses - Mayulu, Hamdi; Annisa Puteri, Sarah Shevi; Anindyasari, Dinar; Daru, Taufan Purwokusumaning; Tricahyadinata, Irsan; Christiyanto, Marry; Rorimpandey, Boyke (Technium Business and Management, 2024)
This research aimed to investigate the profitability of beef cattle fattening businesses in Balikpapan City, Indonesia. To determine the research location, a thorough survey was conducted, and 40 farmers were selected as respondents using a purposive sampling method. The inclusion criteria were ownership of at least 2 beef cattle with a rearing period of over 1 year, engagement in fattening businesses, and proximity to the research area. The data obtained were analyzed through a series of tabulation, correction, and evaluation using profitability analysis which included Net Profit Margin (NPM) and Gross Profit Margin (GPM). Profitability analysis showed that NPM was 54.72% and GPM was 67.33%. Based on the results, it was concluded that beef cattle fattening businesses in the North Balikpapan Sub-district were economically viable and had the potential for sustainable development.